2004
DOI: 10.1002/elps.200405904
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a positively charged cellulose derivative chiral stationary phase with copolymerization reaction for capillary electrochromatographic separation of enantiomers

Abstract: A positively charged chiral stationary phase (CSP) was prepared by chemically immobilizing cellulose 3,5-dimethylphenylcarbamate onto methacryloyldiethylenetriaminopropylated silica (MCDEAPS) via a radical copolymerization reaction. The prepared CSP was evaluated for enantiomer separation in nonaqueous capillary electrochromatography (CEC). Electroosmotic flow (EOF) generated on the prepared CSP could be significantly improved with introduction of positive charges into the CSP, and separation of enantiomers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Recently, those kinds of CSPs were also transferred to CEC. Packed-column CEC with coated or bonded cellulose tris(3,5-dimethylphenylcarbamate) (CDMPC) [14,[25][26][27][28][29][30][31][32], cellulose tris(4-methylbenzoate) [33,34], cellulose tris(3,5-dichlorophenylcarbamate) [35][36][37][38], and amylose (3,5-dimethylphenylcarbamate) [27,34,39] were reported by several research groups. Surprisingly, no attention has been paid to the polysaccharide derivative-based monolithic CSPs for CEC separation, although Chankvetadze et al [40][41][42] reported promising application of such kinds of columns in HPLC and CLC.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, those kinds of CSPs were also transferred to CEC. Packed-column CEC with coated or bonded cellulose tris(3,5-dimethylphenylcarbamate) (CDMPC) [14,[25][26][27][28][29][30][31][32], cellulose tris(4-methylbenzoate) [33,34], cellulose tris(3,5-dichlorophenylcarbamate) [35][36][37][38], and amylose (3,5-dimethylphenylcarbamate) [27,34,39] were reported by several research groups. Surprisingly, no attention has been paid to the polysaccharide derivative-based monolithic CSPs for CEC separation, although Chankvetadze et al [40][41][42] reported promising application of such kinds of columns in HPLC and CLC.…”
Section: Introductionmentioning
confidence: 96%
“…In CEC, cellulose derivatives including cellulose tris(3,5-dimethylphenyl-carbamate) (CDMPC) [10,[28][29][30], cellulose tris(4-methylbenzoate) [31,32], cellulose tris(3,5-dichlorophenylcarbamate) [33][34][35], and amylase(3,5-dimethylphenylcarbamate) [31,32] have also been used for the separations of enantiomers via coating or bonding on silica-based particulate packed columns or monolithic column. Interestingly, little has been reported on the use of cellulose derivatives, such as CDMPC, for the preparation of hydrophilic organic polymeric monolithic CSPs in CEC.…”
Section: Introductionmentioning
confidence: 99%
“…warfarin). In another study, the authors employed a radical copolymerization reaction for the covalent immobilization of a cellulose carbamate derivative [50]. Hence, cellulose 2,3-bis(3,5-dimethylphenylcarbamate)-6-methacrylate was synthesized and grafted onto N-methacryloyl-modified DEAPS.…”
Section: Particle-packed Stationary Phasesmentioning
confidence: 99%